Calf-Cow and Cow-Bull Stimulus; Effect on the Performance, Behaviour and Welfare of Indigenous Cattle and Buffaloes (Indian Journal of Animal Production and Management, 2024)
At many commercial dairy farms, separation  of calves from their mother cows and buffaloes is  practiced. This separation has significant negative  effects on the immunity, health and growth  performance of the calves. To overcome the  possible effects of mother-calf contacts on cyclic  activity, a socially acceptable and inexpensive tool  is biostimulation. Biostimulation is the stimulatory  effect of bulls, using chemical, visual, olfactory,  tactile, and auditory cues to trigger both, behavioral  and endocrine responses in females. This paper  discusses the effects of cow-calf contact systems  and cow-bull stimulus (biostimulation) on  behaviour, performance and welfare of mothers and  their calves especially in indigenous breeds of cattle  and buffaloes. This literature review concludes that  calf-cow contact is very important for both mother  and calves especially in native dairy cattle and  buffaloes. Free choice colostrum feeding for up to  five days to calves and fulltime contact with mother  during this period followed by housing of calves in a  fenceline contact with mothers for about 4-5 months  was found to be an effective strategy to bring out  substantial overall improvement in performance,  health and welfare of both mothers and their calves.  It further shows that the negative consequences on  cow-calf contact in terms of delayed onset of  ovarian cyclicity can be effectively overcome by  keeping a bull in direct or fenceline contact with  mother cows and buffaloes after about a month  after calving.
Keywords: cow-calf contact; cow-bull contact; biostimulation; behaviour; welfare